Battery positive electrode slurry and preparation method thereof
By modifying the double-walled carbon nanotubes with metal frames and adsorption of long-chain benzimidazolyl polymers, and combining polyimide with polyacrylonitrile to form a composite glue solution, the problem of insufficient performance and stability of the cathode material of lithium-ion batteries is solved, and higher energy density and longer service life are achieved.
Patent Information
- Application Number
- CN202411715932.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The performance and stability of the existing lithium-ion battery cathode materials are limited by problems such as body modification complexity and surface coating discontinuity, resulting in insufficient energy density and service life.
By modifying the conductive agent double-walled carbon nanotubes with metal frames, and adsorbing a long-chain benzimidazolyl polymer on its surface using benzene ring adsorption effect, combining polyimide with polyacrylonitrile to prepare branched structures to form a composite adhesive solution, optimizing the performance of the adhesive.
It improves the cycle stability, large-rate discharge capacity and energy density of the battery, and meets the market's demand for higher energy density and longer service life.
Smart Images

Figure CN119517981A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery positive electrode slurry and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have become an ideal power source for electric vehicles and energy storage systems due to their significant advantages such as high energy density, excellent cycle life, high operating voltage, low self-discharge rate and environmental friendliness. With the rapid development of electric vehicles and energy storage technology, the market has put forward higher requirements for the energy density of lithium-ion batteries to meet longer driving range and higher energy storage efficiency. In order to further promote the advancement of lithium-ion battery technology, researchers have focused on the modification of cathode materials and conducted a lot of research and experiments. These modification works include two categories: bulk modification and surface coating. Bulk modification mainly involves technologies such as element doping, core-shell structure design, and transition metal concentration gradient, aiming to improve the performance and stability of the battery. However, the bulk modification process is often complicated and costly, and impurities may also be introduced, affecting the overall performance of the battery. Surface coating usually uses metal oxides as coatings to isolate the cathode material from the electrolyte and reduce the occurrence of side reactions. However, this coating tends to be deposited discontinuously, resulting in poor conductivity and affecting the charge and discharge performance of the battery. In recent years, significant progress has been made in the field of polymer binders. As a key auxiliary component of positive electrode materials, binders play a vital role in the integrity and stability of positive electrode structures. By optimizing the performance of binders, the overall performance of lithium-ion batteries can be further improved to meet the market demand for higher energy density and longer service life. Summary of the invention
[0003] The purpose of the present invention is to provide a battery positive electrode slurry and a preparation method thereof, which are used to optimize the performance of the binder, further improve the overall performance of the lithium-ion battery, and meet the market demand for higher energy density and longer service life.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a positive electrode slurry for a battery comprises the following steps:
[0006] S1. In a nitrogen atmosphere, take polyphosphoric acid and phosphorus pentoxide and mix them, stir at 100°C for 40-50min, cool to 70°C, add 1,2,4,5-benzenetetraamine tetrahydrochloride, heat to 100°C and stir for 6-8h, add 2,5-dihydroxyterephthalic acid, stir for 1-2h, then heat to 120°C and stir for 2h, then heat to 140°C and stir for 2h, then heat to 160°C and stir for 2h, then heat to 180°C and stir for 1h, cool to 120°C, discharge, wash, neutralize and dry to obtain a benzimidazole-based polymer;
[0007] S2, mixing cobalt nitrate hexahydrate, polyvinyl pyrrolidone and methanol, ultrasonically dispersing for 10-15 minutes, adding double-walled carbon nanotubes, and continuing ultrasonic treatment for 10-12 minutes to obtain material A;
[0008] S3, taking the benzimidazole polymer, N-methylpyrrolidone, and methanol, mixing them, ultrasonically treating them for 20-30 minutes, adding the material A, stirring for 1-2 hours, and then standing for 20-30 hours, vacuum filtering, and taking the solid phase and vacuum drying it at 70° C. for 10-12 hours to obtain material B;
[0009] S4, in a nitrogen atmosphere at 5-10°C, mix m-phenylenediamine, 3,5-diaminobenzoic acid and N-methylpyrrolidone, stir for 30-40 min, add 4,4'-oxydiphthalic anhydride, continue stirring for 4-5 h, add 1,3,5-tris(4-aminophenoxy)benzene, continue stirring for 2-3 h, and obtain material C;
[0010] S5, take N-methylpyrrolidone and polyacrylonitrile, mix, stir for 2-3h, obtain material D, and store at low temperature for later use;
[0011] S6, taking the material C and the material D, mixing, stirring for 4-6 hours, to obtain a composite glue solution;
[0012] S7, taking the composite glue, material B, and positive electrode active material, mixing them, and stirring for 20-30 minutes to obtain the battery positive electrode slurry.
[0013] As a preferred technical solution of the present invention, in step S1, the mass ratio of the polyphosphoric acid, phosphorus pentoxide, 1,2,4,5-benzenetetraamine tetrahydrochloride, and 2,5-dihydroxyterephthalic acid is 18:6:1.5-1.6:1.1-1.2; the phosphorus pentoxide content in the polyphosphoric acid is 80%, which is purchased from Nanjing Chemical Reagent Co., Ltd.
[0014] As a preferred technical solution of the present invention, in step S2, the dosage ratio of the cobalt nitrate hexahydrate, polyvinyl pyrrolidone, methanol and double-walled carbon nanotubes is 7.2-7.3 g: 0.5-0.6 g: 250 mL: 0.48-0.53 g.
[0015] As a preferred technical solution of the present invention, in step S3, the dosage ratio of the benzimidazole polymer, N-methylpyrrolidone, methanol, and material A is 25-35 g: 200 mL: 50 mL: 180-200 mL.
[0016] As a preferred technical solution of the present invention, in step S4, the dosage ratio of m-phenylenediamine, 3,5-diaminobenzoic acid, N-methylpyrrolidone, 4,4'-oxydiphthalic anhydride, and 1,3,5-tris(4-aminophenoxy)benzene is 1.23-1.24g: 0.74-0.75g: 70-90mL: 5.44-5.45g: 0.27-0.29g.
[0017] As a preferred technical solution of the present invention, in step S5, the mass ratio of N-methylpyrrolidone to polyacrylonitrile is 19:1.
[0018] As a preferred technical solution of the present invention, in step S6, the mass ratio of material C to material D is 7-8:2-3.
[0019] As a preferred technical solution of the present invention, in step S7, the mass ratio of the composite glue, material B, and positive electrode active material is 3:5:92.
[0020] As a preferred technical solution of the present invention, in step S7, the positive electrode active material is a nickel-cobalt-manganese positive electrode material NCM811, and its chemical formula is a ratio of nickel, cobalt and manganese of 8:1:1.
[0021] The battery positive electrode slurry is prepared by the above-mentioned preparation method.
[0022] Beneficial effects of the present invention:
[0023] A battery positive electrode slurry and a preparation method thereof disclosed in the present invention modify the conductive agent double-walled carbon nanotubes with a metal framework, and use the benzene ring adsorption effect to adsorb long-chain benzimidazole-based polymers on the surface of the double-walled carbon nanotubes. The steric hindrance effect of the long chain helps to prevent the agglomeration of the double-walled carbon nanotubes, while introducing more metal active sites to promote charge transfer and enhance the cycle stability of the electrode, thereby increasing the energy density. A composite glue is formed by preparing a branched polyimide and compounding it with polyacrylonitrile to synergistically improve the electrochemical performance of the battery, and the battery exhibits excellent cycle stability, high-rate discharge capacity and energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described below in conjunction with the accompanying drawings.
[0025] Figure 1These are SEM characterization images of material B prepared in Example 2 of the present invention at different magnifications;
[0026] Figure 2 is a SEM characterization image of a positive electrode sheet prepared by the positive electrode slurry prepared in Example 2 of the present invention;
[0027] Figure 3 This is a SEM characterization image of the positive electrode sheet prepared by the positive electrode slurry prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A battery positive electrode slurry and a preparation method thereof, comprising the following steps:
[0031] S1. In a nitrogen atmosphere, take polyphosphoric acid and phosphorus pentoxide and mix them, stir at 100°C for 40 minutes, cool to 70°C, add 1,2,4,5-benzenetetramine tetrahydrochloride, heat to 100°C and stir for 6 hours, add 2,5-dihydroxyterephthalic acid, stir for 1 hour, then heat to 120°C and stir for 2 hours, then heat to 140°C and stir for 2 hours, then heat to 160°C and stir for 2 hours, then heat to 180°C and stir for 1 hour, cool to 120°C, discharge, wash with water, neutralize, and dry to obtain a benzimidazole-based polymer; the mass ratio of the polyphosphoric acid, phosphorus pentoxide, 1,2,4,5-benzenetetramine tetrahydrochloride, and 2,5-dihydroxyterephthalic acid is 18:6:1.5:1.1; the phosphorus pentoxide content in the polyphosphoric acid is 80%, which is purchased from Nanjing Chemical Reagent Co., Ltd.;
[0032] S2, taking cobalt nitrate hexahydrate, polyvinyl pyrrolidone, and methanol, mixing, ultrasonically dispersing for 10 minutes, adding double-walled carbon nanotubes (purchased from Shanghai Haohong Biomedical Technology Co., Ltd.), and continuing ultrasonic treatment for 10 minutes to obtain material A; the amount ratio of cobalt nitrate hexahydrate, polyvinyl pyrrolidone, methanol, and double-walled carbon nanotubes is 7.2g:0.5g:250mL:0.48g;
[0033] S3, take the benzimidazole polymer, N-methylpyrrolidone, and methanol, mix them, ultrasonically treat them for 20 minutes, add the material A, stir for 1 hour, let it stand for 20 hours, vacuum filter, take the solid phase and vacuum dry it at 70°C for 10 hours to obtain material B; the dosage ratio of the benzimidazole polymer, N-methylpyrrolidone, methanol, and material A is 25g:200mL:50mL:180mL;
[0034] S4. In a nitrogen atmosphere at 5°C, m-phenylenediamine, 3,5-diaminobenzoic acid and N-methylpyrrolidone were mixed and stirred for 30 min, 4,4'-oxydiphthalic anhydride was added, stirring was continued for 4 h, 1,3,5-tris(4-aminophenoxy)benzene was added, stirring was continued for 2 h, and material C was obtained; the dosage ratio of m-phenylenediamine, 3,5-diaminobenzoic acid, N-methylpyrrolidone, 4,4'-oxydiphthalic anhydride and 1,3,5-tris(4-aminophenoxy)benzene was 1.23 g: 0.74 g: 70 mL: 5.44 g: 0.27 g;
[0035] S5, taking N-methylpyrrolidone and polyacrylonitrile, mixing, stirring for 2h, obtaining material D, and storing at low temperature for later use; the mass ratio of N-methylpyrrolidone to polyacrylonitrile is 19:1; the average molecular weight of the polyacrylonitrile is 150,000, purchased from Wuhan Rongcan Biotechnology Co., Ltd.;
[0036] S6, taking the material C and the material D, mixing them, stirring for 4 hours, and obtaining a composite glue solution; the mass ratio of the material C to the material D is 7:2;
[0037] S7. Mix the composite glue, material B and positive electrode active material and stir for 20 minutes to obtain the battery positive electrode slurry; the mass ratio of the composite glue, material B and positive electrode active material is 3:5:92; the positive electrode active material is nickel-cobalt-manganese positive electrode material NCM811, and its chemical formula is nickel, cobalt and manganese in a ratio of 8:1:1.
[0038] Example 2
[0039] A battery positive electrode slurry and a preparation method thereof, comprising the following steps:
[0040] S1. In a nitrogen atmosphere, take polyphosphoric acid and phosphorus pentoxide and mix them, stir at 100°C for 45 minutes, cool to 70°C, add 1,2,4,5-benzenetetramine tetrahydrochloride, heat to 100°C and stir for 7 hours, add 2,5-dihydroxyterephthalic acid, stir for 1.5 hours, then heat to 120°C and stir for 2 hours, then heat to 140°C and stir for 2 hours, then heat to 160°C and stir for 2 hours, then heat to 180°C and stir for 1 hour, cool to 120°C, discharge, wash with water, neutralize, and dry to obtain a benzimidazole-based polymer; the mass ratio of the polyphosphoric acid, phosphorus pentoxide, 1,2,4,5-benzenetetramine tetrahydrochloride, and 2,5-dihydroxyterephthalic acid is 18:6:1.55:1.15; the phosphorus pentoxide content in the polyphosphoric acid is 80%, which is purchased from Nanjing Chemical Reagent Co., Ltd.;
[0041] S2, taking cobalt nitrate hexahydrate, polyvinyl pyrrolidone, and methanol, mixing, ultrasonically dispersing for 12 minutes, adding double-walled carbon nanotubes (purchased from Shanghai Haohong Biomedical Technology Co., Ltd.), and continuing ultrasonic treatment for 11 minutes to obtain material A; the amount ratio of cobalt nitrate hexahydrate, polyvinyl pyrrolidone, methanol, and double-walled carbon nanotubes is 7.25g:0.55g:250mL:0.51g;
[0042] S3, take the benzimidazole polymer, N-methylpyrrolidone, and methanol, mix them, ultrasonicate for 25 minutes, add the material A, stir for 1.5 hours, let it stand for 25 hours, vacuum filter, take the solid phase and vacuum dry it at 70°C for 11 hours to obtain material B; the dosage ratio of the benzimidazole polymer, N-methylpyrrolidone, methanol, and material A is 30g:200mL:50mL:190mL;
[0043] As attached Figure 1 As shown, the morphological features of the cage-like structure framework connected in series on the double-walled carbon nanotubes can be clearly observed.
[0044] S4. In a nitrogen atmosphere at 8°C, m-phenylenediamine, 3,5-diaminobenzoic acid and N-methylpyrrolidone were mixed and stirred for 35 min, 4,4'-oxydiphthalic anhydride was added, stirring was continued for 4.5 h, 1,3,5-tris(4-aminophenoxy)benzene was added, stirring was continued for 2.5 h, and material C was obtained; the dosage ratio of m-phenylenediamine, 3,5-diaminobenzoic acid, N-methylpyrrolidone, 4,4'-oxydiphthalic anhydride and 1,3,5-tris(4-aminophenoxy)benzene was 1.235 g: 0.745 g: 80 mL: 5.445 g: 0.28 g;
[0045] S5, taking N-methylpyrrolidone and polyacrylonitrile, mixing, stirring for 2.5h, obtaining material D, and storing at low temperature for later use; the mass ratio of N-methylpyrrolidone to polyacrylonitrile is 19:1; the average molecular weight of the polyacrylonitrile is 200,000, purchased from Wuhan Rongcan Biotechnology Co., Ltd.;
[0046] S6, taking the material C and the material D, mixing them, stirring for 5 hours, and obtaining a composite glue solution; the mass ratio of the material C to the material D is 7.5:2.5;
[0047] S7. Mix the composite glue, material B and positive electrode active material and stir for 25 minutes to obtain the battery positive electrode slurry; the mass ratio of the composite glue, material B and positive electrode active material is 3:5:92; the positive electrode active material is nickel-cobalt-manganese positive electrode material NCM811, and its chemical formula is nickel, cobalt and manganese in a ratio of 8:1:1.
[0048] Example 3
[0049] A battery positive electrode slurry and a preparation method thereof, comprising the following steps:
[0050] S1. In a nitrogen atmosphere, take polyphosphoric acid and phosphorus pentoxide and mix them, stir at 100°C for 50 min, cool to 70°C, add 1,2,4,5-benzenetetramine tetrahydrochloride, heat to 100°C and stir for 8h, add 2,5-dihydroxyterephthalic acid, stir for 2h, then heat to 120°C and stir for 2h, then heat to 140°C and stir for 2h, then heat to 160°C and stir for 2h, then heat to 180°C and stir for 1h, cool to 120°C, discharge, wash with water, neutralize, and dry to obtain a benzimidazole-based polymer; the mass ratio of the polyphosphoric acid, phosphorus pentoxide, 1,2,4,5-benzenetetramine tetrahydrochloride, and 2,5-dihydroxyterephthalic acid is 18:6:1.6:1.2; the phosphorus pentoxide content in the polyphosphoric acid is 80%, which is purchased from Nanjing Chemical Reagent Co., Ltd.;
[0051] S2, taking cobalt nitrate hexahydrate, polyvinyl pyrrolidone, and methanol, mixing, ultrasonically dispersing for 15 minutes, adding double-walled carbon nanotubes (purchased from Shanghai Haohong Biomedical Technology Co., Ltd.), and continuing ultrasonic treatment for 12 minutes to obtain material A; the amount ratio of cobalt nitrate hexahydrate, polyvinyl pyrrolidone, methanol, and double-walled carbon nanotubes is 7.3g:0.6g:250mL:0.53g;
[0052] S3, take the benzimidazole polymer, N-methylpyrrolidone, and methanol, mix them, ultrasonically treat them for 30 minutes, add the material A, stir for 1-2 hours, let it stand for 30 hours, vacuum filter, take the solid phase and vacuum dry it at 70°C for 12 hours to obtain material B; the dosage ratio of the benzimidazole polymer, N-methylpyrrolidone, methanol, and material A is 35g:200mL:50mL:200mL;
[0053] S4. In a nitrogen atmosphere at 10°C, m-phenylenediamine, 3,5-diaminobenzoic acid and N-methylpyrrolidone were mixed and stirred for 40 min, 4,4'-oxydiphthalic anhydride was added, stirring was continued for 5 h, 1,3,5-tris(4-aminophenoxy)benzene was added, stirring was continued for 3 h, and material C was obtained; the dosage ratio of m-phenylenediamine, 3,5-diaminobenzoic acid, N-methylpyrrolidone, 4,4'-oxydiphthalic anhydride and 1,3,5-tris(4-aminophenoxy)benzene was 1.24 g: 0.75 g: 90 mL: 5.45 g: 0.29 g;
[0054] S5, taking N-methylpyrrolidone and polyacrylonitrile, mixing, stirring for 3h, obtaining material D, and storing at low temperature for later use; the mass ratio of N-methylpyrrolidone to polyacrylonitrile is 19:1; the average molecular weight of the polyacrylonitrile is 250,000, purchased from Wuhan Rongcan Biotechnology Co., Ltd.;
[0055] S6, taking the material C and the material D, mixing them, stirring for 6 hours, and obtaining a composite glue solution; the mass ratio of the material C to the material D is 8:3;
[0056] S7. Mix the composite glue, material B and positive electrode active material and stir for 30 minutes to obtain the battery positive electrode slurry; the mass ratio of the composite glue, material B and positive electrode active material is 3:5:92; the positive electrode active material is nickel-cobalt-manganese positive electrode material NCM811, and its chemical formula is nickel, cobalt and manganese in a ratio of 8:1:1.
[0057] Comparative Example 1
[0058] The difference from Example 2 is that the double-walled carbon nanotubes are not modified with a metal framework, the obtained material B is only a dispersion of double-walled carbon nanotubes, and the other operations and steps remain unchanged.
[0059] Comparative Example 2
[0060] The difference from Example 2 is that the double-walled carbon nanotubes are modified with a metal framework, but during the modification process, the homemade benzimidazole-based polymer is replaced with 2-methylimidazole, and the other operations and steps remain unchanged.
[0061] Comparative Example 3
[0062] The difference from Example 2 is that the mass ratio of the material C to the material D in the composite glue is 10:0.
[0063] Comparative Example 4
[0064] The difference from Example 2 is that the mass ratio of the material C to the material D in the composite glue is 0:10.
[0065] Comparative Example 5
[0066] The difference from Example 2 is that the composite adhesive is an adhesive obtained by uniformly mixing conventional polyvinylidene fluoride as an adhesive and N-methylpyrrolidone as a solvent.
[0067] Preparation of positive electrode:
[0068] The positive electrode slurry prepared in the above Examples 1-3 and Comparative Examples 1-4 was coated on a carbon-containing aluminum foil using a 100 μm scraper and dried at room temperature for 4 h in a clean bench. The slurry was then cut into a circular electrode piece with a diameter of 14 mm. The circular electrode piece was rolled by a roller press, and the rolling density was controlled to be 3 g / cm -3 The circular pole pieces rolled in Examples 1-3 and Comparative Examples 1-4 were placed in a high-temperature oven for programmed temperature treatment, from room temperature to 300°C over 2 hours, and then kept at this temperature for 1 hour for heat treatment; the positive electrode slurry prepared in Comparative Example 5 was coated on a carbon-containing aluminum foil using a 100μm scraper and dried in a vacuum oven at 100°C for 2 hours, and then cut into a circular pole piece with a diameter of 14mm, and the circular pole piece was rolled by a roller press, and the rolling density was controlled to be 3g / cm -3 .
[0069] The positive electrode active material loading in the positive electrode sheets prepared in the above examples 1-3 and comparative examples 1-5 is controlled at 5-6 mg / cm -2 .
[0070] As attached Figure 2-3 As shown, the surface morphology of the positive electrode sheet prepared by the positive electrode slurry prepared in Example 2 is more uniform and compact; the surface morphology of the positive electrode sheet prepared by the positive electrode slurry prepared in Comparative Example 5 is relatively loose and scattered.
[0071] Preparation of negative electrode sheet:
[0072] The negative electrode active material artificial graphite, the conductive agent carbon black Super P, and the binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 92:3:5, and the solvent N-methylpyrrolidone is added, and the mixture is stirred and mixed to obtain the negative electrode slurry. The negative electrode slurry is evenly coated on the surface of the negative electrode current collector, and after coating, it is dried at 80℃-90℃, and then cold pressed, slit, and cut into pieces to obtain the negative electrode sheet.
[0073] Electrolyte preparation:
[0074] A basic electrolyte was prepared, which included dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a mass ratio of 2:1:1. Then, an electrolyte salt was added to make the concentration of lithium hexafluorophosphate in the electrolyte to be 1 mol / L.
[0075] Lithium-ion secondary battery preparation:
[0076] The positive electrode sheet, negative electrode sheet and separator are wound into a battery cell and injected with electrolyte, and then the lithium ion secondary batteries of Examples 1-3 and Comparative Examples 1-5 are prepared through packaging, molding, chemical formation and other processes.
[0077] Performance Testing
[0078] 1) Cycle performance test
[0079] The lithium ion secondary batteries of Examples 1-3 and Comparative Examples 1-5 were tested at 1C / 1C 2.0-4.3V at 25°C, and the gram capacity was tested at 0.1C 2.0-4.3V.
[0080] 2) Energy density test
[0081] At room temperature, charge to 4.2V at 0.33C standard, charge to 0.05C at 4.2V constant voltage, let stand for 10 minutes, discharge to 2.8V at 0.33C, record its discharge capacity, and then calculate the energy density during discharge.
[0082] Energy density (Wh / L) = discharge capacity (Wh) / volume of lithium-ion secondary battery (L)
[0083] The test results are shown in Table 1 below.
[0084] Table 1
[0085]
[0086] It can be seen from Table 1 that the positive electrode slurry prepared in Examples 1-3 of the present application has excellent cycle performance and energy density after being used to prepare lithium-ion batteries; the double-walled carbon nanotubes were not modified in Comparative Example 1, resulting in a decrease in its cycle performance and energy density; although the double-walled carbon nanotubes were framework-modified in Comparative Example 2, the conventional monomer 2-methylimidazole can be attached to the surface of the carbon nanotubes, but it is difficult to suppress the dispersion and agglomeration problem of the double-walled carbon nanotubes, resulting in a decrease in its cycle performance and energy density; Comparative Examples 3-5 only contain a single glue prepared in the present application, and Comparative Example 3 has improved cycle performance and energy density of the positive electrode slurry compared to the polyvinylidene fluoride glue commonly used in the art in Comparative Example 5, but it is far less excellent than the composite glue of the present application, and Comparative Example 4 only contains polyacrylonitrile glue, which is too tightly bonded after heat treatment, resulting in a decrease in the internal electron transport effect, resulting in a significant deterioration in its cycle performance and energy density.
[0087] The present invention modifies the conductive double-walled carbon nanotubes with a metal framework, and uses the benzene ring adsorption effect to adsorb long-chain benzimidazole-based polymers on the surface of double-walled carbon nanotubes. The steric hindrance effect of the long chain helps to prevent the agglomeration of double-walled carbon nanotubes, while introducing more metal active sites, promoting charge transfer and improving the cycle stability of the electrode, thereby increasing the energy density. The branched polyimide is prepared by compounding with polyacrylonitrile to form a composite glue, and the battery exhibits excellent cycle stability, high-rate discharge capacity and energy density. The branched polyimide forms a uniform and continuous coating layer structure on the positive electrode surface. In the process of preparing the positive electrode plate, the polyacrylonitrile is broken and reorganized to form a pyridine-based conjugated polymer by heat treatment, which contains delocalized sp 2 π bonding, synergistically improving the electrochemical performance of the battery.
[0088] The above describes some embodiments of the present invention in detail, but the contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a positive electrode slurry for a battery, characterized in that: The following steps are involved: S1. In a nitrogen atmosphere, polyphosphoric acid and phosphorus pentoxide are mixed, heated and stirred, cooled, 1,2,4,5-benzenetetramine tetrahydrochloride is added, the temperature is gradually increased and stirred, the material is cooled and discharged, washed with water, neutralized, and dried to obtain a benzimidazole-based polymer; S2, mixing cobalt nitrate hexahydrate, polyvinyl pyrrolidone and methanol, ultrasonically dispersing, adding double-walled carbon nanotubes, and continuing ultrasonic treatment to obtain material A; S3, mixing the benzimidazole polymer, N-methylpyrrolidone and methanol, ultrasonically treating, adding the material A, stirring and standing, vacuum filtering, vacuum drying the solid phase, and obtaining material B; S4, in a nitrogen atmosphere and at low temperature, take m-phenylenediamine, 3,5-diaminobenzoic acid, and N-methylpyrrolidone, mix, stir, add 4,4'-oxydiphthalic anhydride, continue stirring, add 1,3,5-tris(4-aminophenoxy)benzene, continue stirring, and obtain material C; S5, taking N-methylpyrrolidone and polyacrylonitrile, mixing, stirring, obtaining material D, and storing at low temperature for later use; S6, taking the material C and the material D, mixing and stirring to obtain a composite glue solution; S7, mixing the composite glue, material B, and positive electrode active material, and stirring to obtain the battery positive electrode slurry.
2. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S1, the mass ratio of the polyphosphoric acid, phosphorus pentoxide, 1,2,4,5-benzenetetraamine tetrahydrochloride, and 2,5-dihydroxyterephthalic acid is 18:6:1.5-1.6:1.1-1.
2.
3. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S2, the dosage ratio of the cobalt nitrate hexahydrate, polyvinyl pyrrolidone, methanol and double-walled carbon nanotubes is 7.2-7.3 g: 0.5-0.6 g: 250 mL: 0.48-0.53 g.
4. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S3, the dosage ratio of the benzimidazole polymer, N-methylpyrrolidone, methanol, and material A is 25-35 g: 200 mL: 50 mL: 180-200 mL.
5. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S4, the ratio of m-phenylenediamine, 3,5-diaminobenzoic acid, N-methylpyrrolidone, 4,4'-oxydiphthalic anhydride and 1,3,5-tris(4-aminophenoxy)benzene is 1.23-1.24 g: 0.74-0.75 g: 70-90 mL: 5.44-5.45 g: 0.27-0.29 g.
6. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S5, the mass ratio of N-methylpyrrolidone to polyacrylonitrile is 19:
1.
7. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S6, the mass ratio of material C to material D is 7-8:2-3.
8. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S7, the mass ratio of the composite glue, material B, and positive electrode active material is 3:5:
92.
9. The method for preparing a positive electrode slurry for a battery according to claim 1, characterized in that: In step S7, the positive electrode active material is a nickel-cobalt-manganese positive electrode material NCM811, and its chemical formula is a ratio of nickel, cobalt, and manganese of 8:1:
1.
10. A battery positive electrode slurry prepared by the preparation method according to any one of claims 1 to 9.